EVALUASI KENYAMANAN DAN AKSESIBILITAS SIRKULASI RUANG IBADAH GEREJA BERDASARKAN STANDARISASI LANSIA (STUDI KASUS: GKI KEBONJATI BANDUNG): EVALUATION OF COMFORT AND ACCESSIBILITY OF WORSHIP SPACE CIRCULATION IN CHURCHES BASED ON ELDERLY STANDARDS (CASE STUDY: GKI KEBONJATI BANDUNG) - Talitha Theophila Sharon; Wibisono, Andriyanto (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2025)
Evaluation Of Comfort And Accessibility Of Worship Space Circulation In Churches Based On Elderly Standards (Case Study: GKI Kebonjati Bandung). Elderly populations represent a vulnerable group requiring special consideration in public space design, including worship facilities. This study evaluates the comfort and accessibility of circulation in the worship space of GKI Kebonjati Bandung based on the standards from PUPR Regulation No. 14 of 2017. A qualitative descriptive  and comparative approach was employed through direct observation, physical measurements, and semi-structured interviews with five elderly congregants, The research reveals two key findings. First, physical conditions showed non-compliance with accessibility standards, including narrow side pathways (70 cm wide), absence of stair handrails, and insufficient seating spacing (30 cm). Second, despite these physical limitations, elderly users reported positive perception comfort due to self-adaptation and established usage patterns. These findings demonstrate that elderly comfort is determined not only by physical space adequacy but also by users' adaptive capacity. The study recommends physical improvements aligned with accessibility standards while establishing a foundation for implementing universal design principles in worship spaces.